The Impact of Food Insecurity on Workers' Productivity in South Sudan (London Journal of Research In Management & Business, 2025)
This paper examined how food insecurity affects worker productivity in South Sudan, a country with a largely agricultural economy that relies on informal employment, but which is currently undergoing civil war and struggling with severe economic problems. Relying on secondary source data and data from the World Bank, and UN agencies databases, the study applied quantitative and qualitative approaches to examine the impact of food shortage on workforce health, truancy, and productivity. While descriptive and correlation analyses showed a negative relationship between FFS and productivity variables. Notably, high levels of food insecurity (60%) were significantly negatively related to both GDP per worker Pearson r =- 0.75, and elevated absenteeism; Pearson r= +0.68. Furthermore, from the interviews, while food insecurity played to the detriment of the workers productivity, some of its effects including tiredness, anxiety, and lack of focus are associated with signs of depression and anxiety and these did display a physical and psychological nature. Comparing the findings with other countries in the East African region brought out how deep the productivity problem is in South Sudan, where workers were over twice as likely not to attend work. In light of this analysis, the paper can definitively establish that food insecurity devastatingly erodes workers output in South Sudan, thereby perpetuating economic near-stagnation. They include supporting agriculture systems, enhancing the structures of food supply to promote a healthy civilian labour force, andnutrition-specific interventions. They could help stabilize the development of the South Sudan economy through the reduction of the direct causes of food insecurity in the workforce.
Keywords: copyright; Literary and Artistic Property; OAPI; ARIPO; Acculturaltion; Legal Anthropology; Comparative Law; communication; soft skills; Training and Development; Quality of care; Health care administrator; Playtech Edu; Educational technology; Educational indicators; Data monitoring; S㯠Miguel dos Campos; sustainable development; Anxiety; Depression; food insecurity; worker productivity; south sudan; agricultural economy; informal employment; economic challenges; civil war; workforce health; absenteeism; gdp per worker; food supply; nutrition interventions